MiR‐9 modulates and predicts the response to radiotherapy and EGFR inhibition in HNSCC. Issue 7 (1st June 2021) - Citron, Francesca; Segatto, Ilenia; Musco, Lorena; Pellarin, Ilenia; Rampioni Vinciguerra, Gian Luca; Franchin, Giovanni; Fanetti, Giuseppe; Miccichè, Francesco; Giacomarra, Vittorio; Lupato, Valentina; Favero, Andrea; Concina, Isabella; et al.
Abstract: Radiotherapy (RT) plus the anti‐EGFR monoclonal antibody Cetuximab (CTX) is an effective combination therapy for a subset of head and neck squamous cell carcinoma (HNSCC) patients. However, predictive markers of efficacy are missing, resulting in many patients treated with disappointing results and unnecessary toxicities. Here, we report that activation of EGFR upregulates miR‐9 expression, which sustains the aggressiveness of HNSCC cells and protects from RT‐induced cell death. Mechanistically, by targeting KLF5, miR‐9 regulates the expression of the transcription factor Sp1 that, in turn, stimulates tumor growth and confers resistance to RT+CTX in vitro and in vivo . Intriguingly, high miR‐9 levels have no effect on the sensitivity of HNSCC cells to cisplatin. In primary HNSCC, miR‐9 expression correlated with Sp1 mRNA levels and high miR‐9 expression predicted poor prognosis in patients treated with RT+CTX. Overall, we have discovered a new signaling axis linking EGFR activation to Sp1 expression that dictates the response to combination treatments in HNSCC. We propose that miR‐9 may represent a valuable biomarker to select which HNSCC patients might benefit from RT+CTX therapy. Synopsis: The combination therapy of Radiotherapy + Cetuximab (RT + CTX) is currently used for the treatment of HNSCC. Its lower toxicity compared to chemotherapy makes it the primary choice for fragile patients. This study identifies miR‐9 as a biomarker of RT + CTX responsiveness and explains why miR‐9 may be especially relevant in TP53 mutated HNSCC. In HNSCC cells, miR‐9 expression is regulated by EGFR activity. High miR‐9 expression confers to HNSCC cells higher tumorigenic activity and resistance to RT + CTX, predicting shorter survival of HNSCC patients treated with RT + CTX. miR‐9 targets the transcription factor KLF5 by binding its 3'UTR. In TP53 mutated context, miR‐9‐mediated silencing of KLF5 causes activation of SP1 that drives tumour progression program of HNSCC and mediates response to therapies. Abstract : The combination therapy of Radiotherapy + Cetuximab (RT + CTX) is currently used for the treatment of HNSCC. Its lower toxicity compared to chemotherapy makes it the primary choice for fragile patients. This study identifies miR‐9 as a biomarker of RT + CTX responsiveness and explains why miR‐9 may be especially relevant in TP53 mutated HNSCC.